The Role of Social-Ecological Resilience in Coastal Zone Management: A Comparative Law Approach to Three Coastal Nations - Garmestani, Ahjond; Craig, Robin K.; Gilissen, Herman Kasper; McDonald, Jan; Soininen, Niko; van Doorn-Hoekveld, Willemijn J.; van Rijswick, Helena F. M. W. (Frontiers in Ecology and Evolution, 2019)
Around the globe, coastal communities are increasingly coping with changing environmental conditions as a result of climate change and ocean acidification, including sea level rise, more severe storms, and decreasing natural resources and ecosystem services. A natural adaptation response is to engineer the coast in a perilous and often doomed attempt to preserve the status quo. In the long term, however, most coastal nations will need to transition to approaches based on ecological resilience—that is, to coastal zone management that allows coastal communities to absorb and adapt to change rather than to resist it—and the law will be critical in facilitating this transition. Researchers are increasingly illuminating law’s ability to promote social-ecological resilience to a changing world, but this scholarship—mostly focused on U.S. law—has not yet embraced its potential role in helping to create new international norms for social-ecological resilience. Through its comparison of coastal zone management in Australia, Finland, and the Netherlands, this article demonstrates that a comparative law approach offers a fruitful expansion of law-and-resilience research, both by extending this research to other countries and, more importantly, by allowing scholars to identify critical variables or variable constellations associated with countries’ decisions to adopt laws designed to promote social-ecological resilience and to identify mechanisms that allow for a smoother transition to this approach. For example, our comparison demonstrates, among other things, that countries can adopt coastal zone management techniques that integrate social-ecological resilience without fully abandoning more traditional engineering approaches to adapt to environmental change and its impacts.